Georgia : Third Review Under the Extended Fund Facility Arrangement-Press Release; Staff Report; Staff Supplement. (IMF Staff Country Reports; Country Report ;, 2018)
Recent economic developments. Economic activity remained strong in 2018H1 but decelerated since due to subdued private construction activity and delays in public infrastructure. Inflation has remained below the 3-percent inflation target in 2018. Higher revenues and lower investment resulted in a fiscal surplus through September 2018. Against the background of high credit growth, the authorities introduced regulations to limit household over-indebtedness. The banking sector remains well capitalized, liquid, and profitable, but dollarization remains high.